Pengaruh Transfer Pricing, Capital Intensity, Komite Audit, dan Profitabilitas terhadap Tax Avoidance - Hidayah, Nurul; Puspita, Dewi Ayu (Universitas Negeri Yogyakarta, 2024)
ABSTRACTThis study aims to examine and analyze the influence of transfer pricing, capital intensity, audit committee, and profitability on tax avoidance in multinational mining companies. The research method employed is quantitative research. The data source for the study consists of annual reports of multinational mining companies listed on the Indonesia Stock Exchange (BEI) for the period 2017-2021. Samples were obtained from as many as 30 data observations with the purposive sampling technique. The hypothesis testing methods used include multiple linear regression, F-test, T-test, and R2 test. The research findings indicate that transfer pricing has a negative effect on tax avoidance, while capital intensity, audit committee, and profitability do not have a significant impact on tax avoidance. Companies that have good transfer pricing management can help reduce tax avoidance practices.Keywords: Transfer pricing, Capital intensity, Audit committee, Profitability, Tax avoidanceABSTRAKPenelitian ini bertujuan untuk menguji dan menganalisis pengaruh transfer pricing, capital intensity, komite audit, dan profitabilitas terhadap tax avoidance pada perusahaan pertambangan multinasional. Metode penelitian ini merupakan penelitian kuantitatif. Sumber data penelitian berupa laporan tahunan perusahaan pertambangan multinasional yang terdaftar di BEI periode 2017-2021. Sampel diperoleh sebanyak 30 data pengamatan dengan teknik purposive sampling. Metode pengujian hipotesis yang digunakan adalah regresi linear berganda, uji F, uji T, dan uji R2. Hasil penelitian menunjukkan bahwa transfer pricing berpengaruh negatif terhadap tax avoidance. Sementara capital intensity, komite audit, dan profitabilitas tidak berpengaruh terhadap tax avoidance. Perusahaan yang memiliki manajemen transfer pricing yang baik dapat membantu mengurangi praktik penghindaran pajak.Kata Kunci: Transfer pricing, Capital intensity, Komite audit, Profitabilitas, Tax avoidance